Sociodemographic profile and future expectations of newly entered students in a dental institute in Greater Noida, India - Vaibhav Motghare; K Jayaprakash; K K Shivalingesh; Bhuvandeep Gupta; Sahil Thakkar; Ishan Prabhakar (Wolters Kluwer Medknow Publications, 2015)
Introduction: Dentistry is one of the most reputed professions all over the world and is becoming a fastest growing career choice for students. Thus, it is necessary to know reasons for choosing dentistry as a career and their future expectations. Aim: The aim was to obtain information about sociodemographic profile, influencing and motivating factors for a career choice and to know future expectations of 1 st year students enrolled in a private dental institute in India. Materials and Methods: A cross-sectional study was conducted by distributing pretested structured questionnaire to 100 1 st year students enrolled in the Institute. The overall response rate was 93%. Statistical analysis was performed using SPSS 20.0 and Chi-square test was applied. Results: Parents were most influencing factors for both male and female students to choose dentistry and students rated reputation and lifestyle (96.7%) as most motivating factor. About 80% of students wanted to pursue specialization after B.D.S where maximum preference was given to oral surgery (29%), endodontics (12%), and orthodontics (9%). Statistically significant association was found between gender and interest to do specialization in dentistry (P = 0.004). Conclusion: Dentistry upholds a reputable position among the students, and most students' want to pursue specialization after completion, of course; however, it's disheartening that very few students are inclined toward nonclinical branches.